Sinergi OJK dan Perbankan dalam Pengelolaan Dana CSR yang Transparan dan Akuntabel - Tazkia Widia Ardani; Wifa Shabilla; Siti Nurhaliza; Dea Rizki Desambari; Zhafira Nasywa Adriyanasta; Mutiara Laude Amabel; Tri Setiady; Meita Fadhilah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The management of Corporate Social Responsibility (CSR) in the banking sector holds strategic importance in strengthening public trust, supporting sustainable development, and ensuring that the distribution of CSR funds aligns with principles of good governance. However, CSR implementation among Indonesian banks continues to face fundamental issues, including limited transparency, inconsistent reporting standards, and weak supervisory mechanisms. This study aims to analyze the synergy between the Financial Services Authority (OJK) and the banking industry in establishing transparent and accountable CSR fund management. Using a normative legal approach combined with institutional analysis, the findings reveal that although OJK has issued sustainable finance regulations such as POJK No. 51/POJK.03/2017, these regulations have not fully ensured the integrity and accountability of CSR distribution. Strengthening reporting standards, ensuring independent audits, and integrating a digital CSR reporting system are essential to enhance oversight. This study proposes a regulatory–institutional synergy model between OJK and the banking sector to build CSR governance that is transparent, participatory, and impact-oriented.